Melagatran prevents tissue factor expression in human platelet-monocyte heterotypic complexes - Belliard, A.; Mauco, G.; Bonnet, M. L.; Hauet, T.; Macchi, L. (Cellular and Molecular Biology, 2008)
Platelets form heterotypic complexes with circulating monocytes, inducing the expression of the procoagulant Tissue Factor (TF) that leads to thrombin generation. We investigated the potential preventive effect of melagatran, a direct anti-thrombin drug, on TF expression by platelet/monocyte heterotypic complexes (PMHC) from healthy human donors. Flow cytometry and western blot analysis were performed to characterize surface and total TF protein expression in PMHC in venous blood samples drawn in the presence of heparin or heparin and melagatran (4µM). Addition of melagatran significantly lowered the percentage of TF positive PMHC (2.6±0.3 vs. 5.9±0.7 %, p<0.01). This was not due to a melagatran-induced decrease in activation of the platelets associated with monocytes in PMHC. Indeed, melagatran effect on TF expression was accompanied by an increase in cell surface P-selectin expression in PMHC (95.6±1.9 vs. 48±18 %, p<0.001), suggesting that platelet were actually more activated in PMHC from the melagatran-treated samples. Western blot analysis of PBMC extracts suggested that melagatran specifically targeted a (54kD) form of TF in monocytes. Although further investigation is warranted, these data suggest that melagatran decreases TF expression in PMHC.